PNPLA3 I148M variant links to adverse metabolic traits in MASLD during fasting and feeding - Lina Jegodzinski; Lorena Rudolph; Darko Castven; Friedhelm Sayk; Ashok Kumar Rout; Bandik Föh; Laura Hölzen; Svenja Meyhöfer; Andrea Schenk; Susanne N. Weber; Monika Rau; Sebastian M. Meyhöfer; et al. (JHEP Reports, 2025)
Background & Aims: The PNPLA3 rs738409 polymorphism is the most abundant genetic risk factor associated with progression of metabolic dysfunction-associated steatotic liver disease (MASLD) to steatohepatitis (MASH) and fibrosis. Although fasting and feeding affect PNPLA3 expression, molecular insights into the pathophysiological influence remain scarce. Methods: We analyzed 353 serum samples of patients with MASLD from two German tertiary centers using nuclear magnetic resonance (NMR)-proteometabolomics. Patients were stratified by PNPLA3 rs738409 C>G genotype: ‘CC’, ‘CG’, and ‘GG’. Metabolites, lipoproteins, and glycoproteins were assessed based on fasting status. Results: PNPLA3 GG displayed a distinct metabolic profile, with notable alterations between fasting and non-fasting states. During the latter, GG carriers showed lower levels of VLDL-1, reflecting impaired triglyceride (TG) efflux from hepatocytes. Following an overnight fast, GG carriers exhibited higher tricarboxylic acid cycle metabolites and ketone bodies, overall indicating increased β-oxidation likely attributed to lower PNPLA3 expression, facilitating unrestricted adipose triglyceride lipase activity and consecutive increased hepatic TG secretion. In addition, the ketogenic amino acid lysine, critical for mitochondrial carnitine transport, was significantly reduced (GG 0.14 ± 0.09 mM vs. CC 0.18 ± 0.08 mM, q = 0.015). Consistently, TGs were enriched in LDL and HDL particles, and an increased number of intermediate-density lipoproteins emerged as a distinct marker in fasted GG carriers (GG 202.9 ± 68.2 mg/dl vs. CC 160.8 ± 65.6 mg/dl, q = 0.007). These metabolic changes were enhanced in patients with type 2 diabetes mellitus and/or obesity. Conclusions: Our findings suggest a dichotomous pattern of increased hepatic lipid storage during feeding and excessive lipid oxidation during fasting, which exceeds metabolic capacity, inducing cellular toxicity in PNPLA3 GG carriers. This interplay fuels a detrimental fasting/non-fasting cycle, thus pointing to the need for preventive strategies. Impact and Implications: The PNPLA3 rs738409 (p.I148M) polymorphism is the most prevalent genetic risk factor for metabolic dysfunction-associated steatotic liver disease progression and is influenced by fasting and feeding cycles. However, the pathophysiological consequences of this regulation remain poorly understood. Nuclear magnetic resonance-proteometabolomics reveals a distinct signature in homozygous PNPLA3 GG carriers that changes significantly with fasting status, providing important implications for diagnosis and preventive strategies.